Digital drugs and their relationship to self-monitoring in adolescents - Gabir, Neran Youssef; Muhammed Salih, Aussad Khudier (Al-Adab Journal, 2022)
The current research aims to identify: 1- Digital drugs in adolescents 2- Self-monitoring of adolescents. 3- The nature of the correlation between self-monitoring and digital drugs according to gender (male - female), and specialization (scientific – human). 4- The differences in the correlation between self-monitoring and digital drugs according to gender (male - female), and specialization (scientific – human). The current research is limited to adolescent students (males and females) in Baghdad schools affiliated to the six districts. The scale was applied to (400) students, who were chosen by the stratified random method. After statistical analysis, the results came to the following: 1- Adolescent students in Baghdad schools have digital drugs. 2- Adolescent students in Baghdad schools enjoy self-monitoring. 3 -There is an inverse negative function relationship between self-monitoring and digital drugs. 4 -There are no statistically significant differences between self-monitoring and digital drugs according to gender (male - female), and specialization (scientific - human).